Photocatalytic degradation of pharmaceuticals pollutants using N-doped TiO 2 photocatalyst: identification of CFX degradation intermediates - Shetty, Rohit; Chavan, Vilas B.; Kulkarni, Prashant Shripad; Kulkarni, Bhaskar D.; Kamble, Sanjay P. (Indian Chemical Engineer, 2017)
The N-doped TiO2 photocatalyst was synthesized by the sol–gel method and characterized in detail in terms of its morphology, structure and composition. The prepared N-doped TiO2 exhibited polycrystalline structure having particle sizes of around 50–120 nm and rod-shaped geometry. The N-doped TiO2 was subsequently used for the photocatalytic degradation (PCD) of pharmaceutical micropollutants, namely ciprofloxacin HCl (CFX), naproxen (NPX) and paracetamol (PARA) and it was found that the rate of degradation of CFX and NPX is higher than that of PARA. To verify the beneficial effect of N-doped TiO2 for PCD of CFX, similar experiments were carried out using commercially available Aeroxide P-25 TiO2. It was observed that N-doped TiO2 was more efficient than Aeroxide® P-25 TiO2. It was also found that the PCD of CFX in the presence of N-doped TiO2 was highly efficient under the solar radiation as compared with artificial radiation. The effect of various operating parameters, such as adsorption of CFX, pH of the aqueous solution, effect of co-existing ions on PCD of CFX, was investigated using artificial radiation and optimum conditions were established. The intermediates formed during the PCD of CFX were identified using liquid chromatography tandem mass chromatography (LC-MS/MS). The presented results demonstrate that N-doped TiO2 photocatalyst shows excellent photocatalytic activity in the visible region for the degradation of pharmaceutical pollutants.